Chemical characterization, assessment of acute oral toxicity, and antinociceptive potential of the methanolic extract of Montrichardia linifera (Arruda) Schott leaves from Brazil - Costa, Wellington Junior Taisho Nagahama; Coelho, Leticia Prazeres de Farias; Tembra, Alan Luz; Monteiro, Rayan Fidel Martins; Almeida, Jose Ramon Gama; Lima, Klinsmann Thiago; Botelho, Anderson de Santana; Batista, Raimundo Junior da Rocha; Freitas, Jofre Jacob da Silva; Pinheiro, Wandson Braamcamp de Souza; Oliveira, Fabiola Raquel Tenorio; Oliveira, Karen Renata Herculano Matos; et al. (Frontiers in Pharmacology, 2024)
Background: Montrichardia linifera (Arruda) Schott is popularly known as “aninga”, “aningaçu”, “aningaíba” and “aninga-do-igapó”. Compresses and plasters made from the leaves of this medicinal plant are used to treat abscesses, tumors, and pain caused by stingray stings. Aim of the study: This study aimed to chemically characterize the methanolic extract of Montrichardia linifera leaves (MEMLL), as well as to verify its acute oral toxicity and its antinociceptive potential. Materials and methods: The leaves were collected during the rainy season, and the methanolic extract was obtained after gradient extraction using different solvents. The MEMLL was analyzed using high-performance liquid chromatography (HPLC) and Nuclear Magnetic Resonance (NMR). Acute oral toxicity testing followed the Organization for Economic Co-operation and Development (OECD) guidelines 423. Subsequently, acetic acid, hot plate, and formalin tests were used to evaluate the analgesic effects. Results: In the chemical characterization of MEMLL by HPLC, three flavonoids were identified: rutin, quercetin, and epicatechin. In addition, when NMR spectroscopy was performed, rutin and quercetin were again identified, as well as the chemical compounds luteolin and chrysoeriol. In the acute oral toxicity test, the MEMLL showed no physiological or behavioral changes. In the nociceptive study, MEMLL showed an effect at doses of 50 and 100 mg/kg in the 0.6% acetic acid test, 51.46% and 75.08%, respectively. In the hot plate test, the MEMLL group at a dose of 50 mg/kg was effective at times of 30 and 60 min, 164.43% and 122.95%, respectively. Similarly, the MEMLL group at a dose of 100 mg/kg was also effective in increasing latency at times of 30 and 60 min, 162.62% and 136.68%, respectively. In the formalin test, the antinociceptive effect in the neurogenic pain with MEMLL at doses of 50 and 100 mg/kg when compared to the control group, 35.25% and 52.30%, respectively. In the inflammatory phase, inhibition was observed in MEMLL at doses of 50 and 100 mg/kg, 66.39% and 72.15%, respectively. Conclusion: The MEMLL has analgesic properties and is non-toxic, validating the Brazilian ethnopharmacological use of this plant for pain treatment. The leaves of the species Montrichardia linifera showed central and peripheral antinociceptive effects.